Quantifying the influence of wind power and photovoltaic on future electricity market prices. (15th January 2019) - Sorknæs, Peter; Djørup, Søren Roth; Lund, Henrik; Thellufsen, Jakob Zinck
Highlights: Increasing variable renewable electricity sources has shown to lower market prices. Researchers have investigated this effect using historical data electricity markets. Here holistic energy system analyses are done with an energy system simulation tool. The analyses are used to quantify the effect on a specific case. Abstract: Variable renewable electricity sources have been shown to reduce wholesale electricity market prices. This is expected to reduce the incentive for investments in new electricity production capacity, and might even make these investments infeasible, if relying only on the income from trade on the current electricity market paradigms. In this paper, a novel approach for quantifying this effect in future energy systems is developed using a holistic energy system approach. The approach is applied to the case of Denmark in 2015, which is part of the Nordic and Baltic wholesale electricity market Nord Pool Spot. A holistic energy system model is created and verified according to both the Danish energy balance and the Nord Pool Spot system price in 2015. Using this verified model, the Nord Pool Spot system price is quantified at increasing amounts of onshore wind power, offshore wind power and photovoltaic in Denmark. It is found that regardless of which variable renewable electricity source is implemented, including a combination of the three, the Nord Pool Spot system price decreases as the amount of energy produced by these sources increases, and this effect occurs immediately as more is introduced.